A case control study on risk factors associated with drug addiction amongst Malaysian males - Md. Zain, Azhar; Lekhraj Rampal, Sanjay Rampal; Gyanchand Rampal, Lekhraj Rampal (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2007)
Objectives: Drug addiction poses a significant threat to the health, social and economic fabric of families, communities and nations. The aim of this study was to determine factors associated with drug addiction amongst Malaysian males. Methods: A population-based case control study was carried out in Johor state. Cases were defined as confirmed male drug dependents aged 15 and above. Controls were defined as those aged 15 and above who had never used illegal drugs in their lifetime. A total of 1016 cases were selected at random from a list obtained from the state anti-drug agency and 1106 controls were sampled from a population-based sampling frame. After obtaining verbal consent, they were interviewed by trained graduates. Multiple logistic regression analysis was performed using Stata V8.2. The final model was adjusted for smoking, age, alcohol consumption, importance of religion, ethnicity, education level and self-esteem. Results: The final model had good fit (p>0.05) and good discrimination (AUC=0.94). Compared with those aged 15-19 years, the highest risk was amongst the 20-29 years age group (adjusted OR(aOR) 7.2; 95%CI=3.8,13.7) followed by the 30-39 year age group (aOR 5.4; 95%CI=2.9, 10.2) and 40-49 year age groups (aOR 5.0; 95 %CI=2.6, 9.8). Being an ever-smoker was highly associated with drug addiction (aOR 98.7; 95%CI=28.7, 339.5). Compared with the Chinese, Malays (aOR 7.4; 95%CI=4.9, 11.2) and Indians (aOR 3.8; 95%CI=2. 1,7.0) had a higher risk of drug addiction. Drug addiction was associated with disagreeing "that religion is important as guidance in their life" (aOR 16.2;95 %CI=8.3, 31.9), and a history of alcohol consumption (aOR 7.6; 95%CI=5.6, 10.4). Conclusion: In conclusion the important risk factors associated with drug addiction is smoking, ethnicity, age, education level, alcohol consumption and not giving importance to religion as guidance in their life. However an increased self-esteem (aOR 0.6; 95%CI=0.4,0.5) is protective against drug addiction.